The THE CONTRIBUTION OF THE OIF IN POLITICAL MATTERS IN THE REPUBLIC OF CONGO FROM 1981 TO 2021 - Nzoussi, Hilaire Kevin (International Journal of Social Service and Research, 2024)
The Organization Internationale de la Francophonie (OIF) has played an important role in shaping the political landscape of the Republic of Congo over the four-decade timeframe. The study employed a historical and qualitative research approach, focusing on the analysis of political cooperation between the OIF and the Congo from 1981 to 2021. The research used a literature review to explore historical events, political reforms, and the impact of OIF's involvement in Congo's political landscape. The data were analyzed through thematic analysis, identifying key themes related to the political evolution of Congo, the organization's role in fostering democracy, peace, and human rights, and its outcomes of their collaboration. The analysis concludes that OIF has played a significant role in the promotion of democracy and peace in Congo through various initiatives.